Assessment of some cultural experimental methods to study the effects of antibiotics on microbial activities in a soil: An incubation study - Molaei, Ali; Lakzian, Amir; Haghnia, Gholamhosain; Astaraei, Alireza; Rasouli-Sadaghiani, MirHassan; Teresa Ceccherini, Maria; Datta, Rahul (PLoS One, 2017)
Oxytetracycline (OTC) and sulfamethoxazole (SMX) are two of most widely used antibiotics in livestock and poultry industry. After consumption of antibiotics, a major portion of these compounds is excreted through the feces and urine of animals. Land application of antibiotic-treated animal wastes has caused increasing concern about their adverse effects on ecosystem health. In this regard, inconsistent results have been reported regarding the effects of antibiotics on soil microbial activities. This study was conducted based on the completely randomized design to the measure microbial biomass carbon, cumulative respiration and iron (III) reduction bioassays. Concentrations of OTC and SMX including 0, 1, 10, 25, 50, and 100 mg/kg were spiked in triplicate to a sandy loam soil and incubated for 21 days at 25°C. Results showed that the effects of OTC and SMX antibiotics on cumulative respiration and microbial biomass carbon were different. SMX antibiotic significantly affected soil microbial biomass carbon and cumulative respiration at different treatments compared to control with increasing incubation time. OTC antibiotic, on the other hand, negatively affected cumulative respiration compared to control treatment throughout the incubation period. Although OTC antibiotic positively affected microbial biomass carbon at day one of incubation, there was no clear trend in microbial biomass carbon between different treatments of this antibiotic after that time period. Nevertheless, sulfamethoxazole and oxytetracycline antibiotics had similar effects on iron (III) reduction such that they considerably affected iron (III) reduction at 1 and 10 mg/kg, and iron (III) reduction was completely inhibited at concentrations above 10 mg/kg. Hence, according to our results, microbial biomass carbon and cumulative respiration experiments are not able alone to exhibit the effect of antibiotics on soil microbial activity, but combination of these two experiments with iron (III) reduction test could well display the effects of sulfamethoxazole (SMX) and oxytetracycline (OTC) antibiotics on soil biochemical activities.
Keywords: půdní mikrobiologie; oxidace-redukce; Írán; Iran; antibakteriální látky; Anti-Bacterial Agents; biomasa; Biomass; Iron; Oxidation-Reduction; železo; Soil Microbiology